Meningkatkan Kualitas Sumber Daya Manusia Melalui Pelatihan Manajemen Sumber Daya Manusia yang Tertata dan Terkoordinasi Guna Membangun Wisata di Kabupaten Kepulauan Seribu, Provinsi DKI Jakarta - Wenny Desty Febrian; Bias Yulisa Geni; Rr Nadhira Harsari Harsari (Yayasan REDI Tiga Monas, 2023)
The importance of improving the quality of human resources in the Kepulauan Seribu Regency through organized and coordinated human resource management training in order to build the Kepulauan Seribu Regency tourism opportunity to become an idol of tourist attractions in Indonesia. Because the determination of good or bad performance will depend on the quality of human resource management. In this case, the participants are employees of the district head's office, the community, and all related elements in the Kepulauan Seribu Regency, DKI Jakarta Province. The purpose of this community service is that with this activity it can improve the quality of existing human resources so that they are able to provide knowledge and insight about the quality of human resources that are able to compete with other regions. Finally, an organized and coordinated quality of human resource management was formed which opened up opportunities for the Kepulauan Seribu Regency, DKI Jakarta Province to become an idol of tourist attractions in Indonesia.